The impact silver nanoparticles on MHD free convection flow of Jeffrey fluid over an oscillating vertical plate embedded in a porous medium - Mohd. Zin, N. A. (Elsevier B.V., 2016)
This article studies the influence of copper nanoparticles (CuNPs) and silver nanoparticles (AgNPs) on the unsteady magnetohydrodynamic (MHD) free convection flow of Jeffrey fluid over an oscillating vertical plate embedded in a saturated porous medium. Nanoparticles (CuNPs and AgNPs) are suspended in Kerosene oil which is chosen as a conventional base fluid. Appropriate dimensionless variables are employed to the governing equations and the exact solutions are obtained for velocity and temperature fields using the Laplace transform technique. The results for various controlling parameters for both CuNPs and AgNPs are shown graphically and discussed in details. Expressions for skin friction and Nusselt number are also evaluated and presented in tabular forms. It has been observed that, an increase of volume fraction leads to the enhancement of velocity and temperature distributions. On the other hand, Hartmann number tends to resist the fluid flow due to the Lorentz force. A comparative study of the present results with the results from the earlier works provides an excellent agreement.